Perceived Work climate and Performance in security Organizations The Case of ABU DHABI POLICE - Al Harethi, Bader (2010)
The purpose of this study is to examine the potential relationships between perceived work climate and job performance in security organizations. Furthermore, the relationship of various factors related to work climate and job performance are studied and investigated. Also, the significance of innovation, commitment, work enthusiasm, and understanding work duties are inspected. The present study also show the interactional consequence of perceived physical and psycho-social work environment on job performance, job satisfaction, and perceived organizational efficiency. Additionally, it emphasizes the significant roles of managers and supervisors in motivating and improving the work climate with the aim of enhancing the job performance. The subject organization of this dissertation is ABU DHABI POLICE Organization. This research focuses on work climate, and how it affects job performance. This study conducted in ABU DHABI POLICE, a security organization located in Abu Dhabi. In this dissertation, self-managed questionnaires were distributed at random way to a sample of 500 full-time employees with the intention of collecting the required data. The results show that well-built organizational climate is positively and completely interrelated with job performance. However, this study draws attention to the significance of organizational climate in enhancing and increasing the job performance in organizations.